Human endothelial cell-derived exosomal microRNA-99a/b drives a sustained inflammatory response during sepsis by inhibiting mTOR expression - Fitzpatrick, Glenn; Nader, Danielle; Watkin, Rebecca; McCoy, Claire E.; Curley, Gerard F.; Kerrigan, Steven W. (Frontiers in Cellular and Infection Microbiology, 2022)
The pathophysiology of sepsis and its accompanying hyper-inflammatory response are key events that lead to multi-organ failure and death. A growing body of literature now suggests that the vascular endothelium plays a critical role in driving early events of sepsis progression. In this study, we demonstrate how endothelial-derived exosomes contribute to a successive pro-inflammatory phenotype of monocytes. Exosomes isolated from S. aureus infected endothelial cells drive both CD11b and MHCII expression in monocytes and contribute dysregulated cytokine production. Conversely, healthy endothelial exosomes had no major effect. microRNA (miRNA) profiling of exosomes identified miR-99 upregulation which we hypothesised as driving this phenotypic change through mechanistic target of rapamycin (mTOR). Knockdown of mTOR with miR-99a and miR-99b mimetics in S. aureus infected monocytes increased IL-6 and decreased IL-10 production. Interestingly, inhibition of miRNAs with antagomirs has the opposing effect. Collectively, endothelial exosomes are driving a pro-inflammatory phenotype in monocytes through dysregulated expression of miR-99a and miR-99b.